Potential distribution of selected invasive alien plants under current and future climate change scenarios in South Africa - Mengistu, Achamyeleh G.; Tesfuhuney, Weldemichael A.; Woyessa, Yali E.; Steyn, Abraham S. (Elsevier, 2023)
Invasive alien plants are one of the main causes for the decline of native biodiversity worldwide. Hence, it is crucial to understand the dynamics of invasive plants in the context of a changing climate. The main aim of this study was to evaluate the potential distribution of two major invasive alien plants, Prosopis spp and Acacia mearnsii, under current and future climate change scenarios across South Africa. The maximum entropy (MaxEnt) model was used with species occurrence data and bioclimatic variables. The Species occurrence data was obtained from the Global Biodiversity Information Facility (GBIF), while the bioclimatic variables were downloaded from the WorldClim database. The model evaluation metrics for training and test samples were the area under curve (AUC) of 0.76 and 0.77 for Prosopis spp, and 0.91 and 0.89 for A. mearnsii, respectively. It showed that MaxEnt performed well in mapping the distribution of both species. Model results indicated that the near-current potential distribution of Prosopis spp and A. mearnsii in South Africa is significant (93.8% and 9.7% of the total land area, respectively). With the projected climate, Prosopis spp showed an inconsistent result across the General Circulation Models (GCMs), projection times and climate change scenarios. However, with respect to the current potential distribution, the geographical ranges of A. mearnsii will significantly contract (by about 75%) due to climate change. Therefore, it is imperative that policy makers, environmental managers and other stakeholders implement integrated management and control strategies to restrict the distribution of Prosopis spp.
Keywords: MaxEnt model; climate change; South Africa; prosopis spp; a. mearnsii; potential distribution; invasive alien plants